The Effect Of Working Capital On Profit In Automotive Companies Listed On The Indonesia Stock Exchange (Idx) - Dono Bonardo Pasaribu (JURNAL ILMIAH SOCIO SECRETUM, 2023)
The purpose of this study was to determine the effect of working capital on profitability in manufacturing companies listed on the Indonesia stock exchange in 2018-2020. The research object used is limited to automotive companies listed on the Indonesia Stock Exchange with the population in this study as many as 12 automotive sector companies. With a sample of 9 companies so that the amount of data obtained is 27 data. The data collection technique uses documentation techniques with the collection of financial statements from each sample published on the www.idx.co.id website. The data used is quantitative data in the form of secondary data. The data collection method used is literature and field research, the analytical method used is descriptive statistics, classical assumption test, simple linear regression analysis and hypothesis testing in the form of partial significant test (t test). The simple linear regression equation is Y = 0.036 + 0.012 X. As for the results of the research that has been done, it is concluded that working capital has an effect on profit which can be seen from the t value > t table 1.706.). The correlation coefficient (R) is 0.485 which states that the correlation between working capital and profit is low. The results of R square with a value of 0.205 or 20.5% of the variables of profit are explained by the independent variable (working capital) while the remaining 79.5% is explained by other variables not examined by the author. As for suggestions to automotive companies listed on the Indonesia Stock Exchange in this study, it has been proven that working capital is very influential on profits, so working capital should be used effectively so that profits increase, if profits increase then in the following year working capital will also increase and vice versa.